The impact of entrepreneurial leadership on innovative employee behavior: A multi-group analysis comparing the United States, Serbia, and Bosnia and Herzegovina - Kreiner Jesa; Sajfert Dragana; Vasić Živorad; Jančev Nikola; Živković Milorad (Journal of Engineering Management and Competitiveness, 2022)
In the research of this paper, the center of events is entrepreneurial leadership as a new concept for the work behavior of associates. This study aims to determine the entrepreneurial self-efficiency and inclination of entrepreneurs towards innovation and creativity of entrepreneurs. The research aims to achieve results that reveal the relationship between entrepreneurial leadership and the work behavior of employees. The study tested 360 individuals - subordinates in small and medium enterprises operating in the United States - California, Serbia - Vojvodina, and Belgrade, and Bosnia and Herzegovina - Republika Srpska. Based on the obtained results, a model was made and hypotheses were tested. It was a big problem to harmonize the results of research from these three regions. Careful processing of the data resulted from these results. The results obtained have a significant effect on innovative entrepreneurship, which again aims to determine whether there is entrepreneurial leadership and in what form. The research found that innovative entrepreneurs mediate between entrepreneurial leadership and the innovative behavior of associates. The results obtained in this study confirm the hypothesis that entrepreneurial self-efficiency has an adequate effect on the connection between entrepreneurial leadership and the innovative behavior of employees in the companies in which they work. The results of this research work are intended to achieve the originality of entrepreneurship and small and medium enterprises dealing with innovation and a challenging business environment. According to the findings of numerous authors who deal with this issue, this research is not the first attempt to develop innovative behavior of employees in entrepreneurial small and medium enterprises, but it certainly has a great impact on increasing the effectiveness of entrepreneurial leadership on innovative behavior.